Frequency and Demographic Profile of Odontogenic Cysts Diagnosed at Tripoli University Hospital, Libya - Shanab, Asmaa; Dunya Ben Sofia; Sarah Shanab (AlQalam Journal of Medical and Applied Sciences, 2024)
Odontogenic cysts are a group of lesions that exclusively affect the oral and maxillofacial regions. The current study aimed to determine the relative frequency and demographic features of odontogenic cysts diagnosed histologically at Tripoli University Hospital and to compare our findings with the latest reports. A 22-year retrospective study of odontogenic cysts histologically diagnosed at Tripoli University Hospital, Tripoli, Libya, archived from 2002 to 2023 was performed. Demographic data including, gender, age at diagnosis, location of lesion, and histopathological diagnosis, were collected and analyzed retrospectively. The diagnosis was according to the latest criteria of the 2022 World Health Organization classification. Odontogenic cysts constituted 9.7% of all 2334 registered orofacial biopsy specimens. A total of 227 cases of histologically diagnosed odontogenic cysts were analyzed. Of these, 129 (56.8%) were inflammatory cysts and 98 (43.2%) were developmental cysts. Apical radicular was the most common type of cyst (54.2%), followed by dentigerous cyst (31.3%), and odontogenic keratocyst (5.3%). A slight male predilection was observed with an overall male-to-female ratio of 1.2:1. The age range was from 5 to 85 years with an overall mean age of 33 ± 15.16 years. The peak incidence was in the third and fourth decades of life. The posterior regions of the jaws were the most prevalent sites (34.4%) for all studied cysts. The demographic profile of the odontogenic cysts in this cohort is similar to previous reports in Libyan and other worldwide populations. الأكياس السنية المنشأ هي مجموعة من الآفات التي تؤثر حصريا على مناطق الفم والوجه والفكين. تهدف الدراسة الحالية إلى تحديد التكرار النسبي والسمات الديموغرافية للأكياس السنية المشخصة نسيجيا في مستشفى طرابلس الجامعي ومقارنة نتائجنا بأحدث التقارير. دراسة رجعية لمدة 22 سنة للأكياس السنية التي تم تشخيصها نسيجيا في مستشفى طرابلس الجامعي، طرابلس، ليبيا، مند سنة 2002 إلى سنة 2023 تم إجراؤها. تم جمع وتحليل البيانات الديموغرافية بما في ذلك الجنس والعمر عند التشخيص وموقع الآفة والتشخيص النسيجي المرضي بأثر رجعي. كان التشخيص وفقا لأحدث معايير تصنيف منظمة الصحة العالمية لعام 2022. شكلت الأكياس السنية المنشأ 9.7% من جميع عينات خزعة الفم والوجه المسجلة البالغ عددها 2334 عينة. تم تحليل 227 حالة من الأكياس السنية المشخصة نسيجيا. من بينهم، كان هناك عدد 129 (56.8%) من الأكياس الالتهابية وعدد 98 (43.2%) من الأكياس التنموية. كان الكيس الجذر القمي هو النوع الأكثر شيوعا من الأكياس (54.2%)، يليه الكيس السني (31.3%)، والكيسة القرنية السنية (5.3%). لوحظ ميل طفيف للذكور مع نسبة إجمالية من الذكور إلى الإناث تبلغ 1.2: 1. وتراوحت الفئة العمرية بين 5 و85 سنة بمتوسط عمر إجمالي يتراوح بين 33 ± 15.16 سنة. كانت ذروة الإصابة في العقدين الثالث والرابع من العمر. كانت المناطق الخلفية من الفكين هي المواقع الأكثر شيوعا (34.4%) لجميع الأكياس السنية المدروسة. يتشابه الملف الديموغرافي للأكياس السنية المنشأ في هذه المجموعة مع التقارير السابقة في السكان الليبيين وغيرهم من السكان في جميع أنحاء العالم